Strategi Pengembangan Manajemen Sumber Daya Manusia dalam Meningkatkan Kinerja Karyawan PT CSM Labuhan Bilik - Diana Diana; Daslan Simanjuntak (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze human resource management development strategies in improving employee performance at PT CSM Labuhan Bilik, as well as to identify its supporting and inhibiting factors. The research method used is descriptive quantitative with a sample of 83 respondents. Data analysis was conducted using multiple linear regression analysis through SPSS software. The partial research results indicate that the HRM Strategy variable (X1) has a significant effect on employee performance with a regression coefficient value of 0.304 and a significance value of 0.004. The HRM Development variable (X2)also has a significant effect with a coefficient value of 0.326 and a significance value of 0.017. Simultaneously (F-test), both variables have a positive and significant effect on employee performance with an F-count of 4.125 > F-table 3.21 and a significance of 0.023. The forms of strategies implemented include education, training, career development, and coaching. The main supporting factors are management commitment and employee motivation, while the inhibiting factors include limited operational time and a non-digitalized monitoring system. The conclusion of this study confirms that the integration of appropriate management strategies and sustainable development programs significantly improves the quality, quantity, and work responsibility of employees at PT CSM Labuhan Bilik.